2006
DOI: 10.1186/1471-2474-7-38
|View full text |Cite
|
Sign up to set email alerts
|

Knee complaints vary with age and gender in the adult population. Population-based reference data for the Knee injury and Osteoarthritis Outcome Score (KOOS)

Abstract: Background: Self-reported knee complaints may vary with age and gender. Reference data from the adult population would help to better interpret the outcome of interventions due to knee complaints. The objectives of the present study were to describe the variation of self-reported knee pain, function and quality of life with age and gender in the adult population and to establish population-based reference data for the Knee injury and Osteoarthritis Outcome Score (KOOS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
322
11
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(366 citation statements)
references
References 25 publications
26
322
11
7
Order By: Relevance
“…As expected, the overall KSS2011 and KOOS decreased with age in the current study, as has been previously reported in other populations [19][20][21]. The results reported here are consistent with those previous findings.…”
Section: Discussionsupporting
confidence: 83%
“…As expected, the overall KSS2011 and KOOS decreased with age in the current study, as has been previously reported in other populations [19][20][21]. The results reported here are consistent with those previous findings.…”
Section: Discussionsupporting
confidence: 83%
“…[22] Our population was young and homogenous with regard to physical activity with a mean age of 22 years, ranging from 14 to 39 years, and large variations in knee function within this group may thus not be likely. However, knee injuries are common in football and thus a worse than population norm knee function may be possible.…”
Section: Discussionmentioning
confidence: 88%
“…[22] This indicates that KOOS scores from a population-based sample are not comparable to KOOS scores derived from persons of the same age group but with a physically active lifestyle.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In one of the few reports looking at patient satisfaction following total knee replacement, Robertsson et al [16] reported on 27,372 patients having had a total knee replacement and reported 18% of women were unsatisfied or uncertain, compared with 16% of men. There were no preoperative evaluations in that series and it is critical that one considers the baseline differences in the population to begin with, as Paradowski et al [15] demonstrated that in a general population survey women had more knee-related complaints than men.…”
Section: Discussionmentioning
confidence: 99%